Pengaruh Budaya Organisasi, Komunikasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan ( Studi pada Pabrik PR DD Tajinan Malang ) - Siti Nadhiroh; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrack This study aims to determine the effect of organizational culture, communication, and work discipline on employee performance at the PR Factory DD Tajinan Malang. The population in the study who were recorded as permanent employees was predominantly male with an average high school education. The analytical technique used in this research is Multiple Linear Regression Analysis. The influence of organizational culture, communication, and work discipline simultaneously has a positive and significant effect on employee performance at the PR factory DD Tajinan Malang. Organizational culture has a partial effect on the performance of employees of PR DD Tajinan Malang factory. Communication has a significant effect on the performance of employees of PR DD Tajinan Malang factory. Discipline has a partial effect on the performance of employees of PR DD Tajinan Malang factory. Keywords: Organizational Culture, Communication, Work Discipline, Employee Performance